Gambaran Penggunaan Galaktagog Di Wilayah Kerja Puskesmas Arjasa Kabupaten Situbondo : Gambaran Penggunaan Galaktagog Di Wilayah Kerja Puskesmas Arjasa Kabupaten Situbondo - DIANA LADY YUNITA HANDOYO; SRI NUR ATIQAH; SITI ZAMILATUL AZKIYAH (Universitas Hang Tuah, 2023)
Of all the cities/regencies in East Java, there are 15 districts that have met the target, while 23 other districts/cities have not yet reached the target. Overall, the achievement of the province of East Java has not been able to meet the target set in 2016 which is 50%. The purpose of this study was to find out the description of the use, perceived effectiveness and perceived side effects of using galactagogues as a breastmilk booster. This study used a cross-sectional method. The research instrument used was a questionnaire with a total of 32 respondents. The results showed that the galactagogue used was 100% herbal galactagogue. The use of galactagogue gave the highest increase in milk production by 21.14% with signs that the baby was not satisfied. The side effects that arise in breastfeeding mothers when using galactagogues are that 55.88% of respondents said they did not experience side effects, 38.23% said they experienced side effects of weight gain, and 2.94% experienced side effects of drowsiness and weakness. Keywords: Herbal Galactagogue, Chemical Galactagogue, Breast Milk Boost